2017
DOI: 10.3389/fcimb.2017.00443
|View full text |Cite
|
Sign up to set email alerts
|

Corilagin Counteracts IL-13Rα1 Signaling Pathway in Macrophages to Mitigate Schistosome Egg-Induced Hepatic Fibrosis

Abstract: The IL-13Rα1 signaling pathway and M2 macrophages play crucial roles in schistosome egg-induced hepatic fibrosis via the expression of pro-fibrotic molecules. This study aims to investigate the inhibitory effect and mechanism of action of corilagin on schistosome egg-induced hepatic fibrosis via the IL-13Rα1 signaling pathway in M2 macrophages in vitro and in vivo. The mRNA and protein expression of IL-13Rα1, PPARγ, KLF4, SOCS1, STAT6, p-STAT6, and TGF-β was measured in vitro with corilagin treatment after IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 56 publications
(61 reference statements)
2
27
0
Order By: Relevance
“…Our present study now reconcile such observations, demonstrating that PZQ has potential preventive antifibrotic effects while it has no efficacy in therapeutically reversing established fibrosis. This conclusion reliably recapitulates the established view of most authors on the subject 9,11,21,[53][54][55][56][57][58][59][60][61][62][63] where PZQ antifibrotic / anti-pathological potential in clinically fibrotic schistosomiasis-diseased patients might not be direct and/or effective on established fibrosis but entirely consequent to its anti-parasitic effect when administered after fibrosis development.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our present study now reconcile such observations, demonstrating that PZQ has potential preventive antifibrotic effects while it has no efficacy in therapeutically reversing established fibrosis. This conclusion reliably recapitulates the established view of most authors on the subject 9,11,21,[53][54][55][56][57][58][59][60][61][62][63] where PZQ antifibrotic / anti-pathological potential in clinically fibrotic schistosomiasis-diseased patients might not be direct and/or effective on established fibrosis but entirely consequent to its anti-parasitic effect when administered after fibrosis development.…”
Section: Discussionsupporting
confidence: 85%
“…The extensive usage of PZQ during mass drug administration campaigns in flatworm-endemic areas has considerable health benefits for the target populations over time such as improved fitness, improved cognitive functions and reduced tissue fibrosis 13,[15][16][17][18][19][20]34,[40][41][42][43][44][45][46][47][48][49][50][51][52] . Whereas most authors associated such health benefits and particularly the improvement of tissue fibrosis in helminth-infested individuals to the sole antiparasitic potential of PZQ 9,11,21,[53][54][55][56][57][58][59][60][61][62][63] , recent reports on the drug ability to also directly mitigate tissue fibrosis have also emerged 13,[15][16][17][18][19][20]34,[40][41][42][43]…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the hepatoprotective effect of Cori has been brought into focus by current research. Several studies reported the protective role of Cori against hepatocellular carcinoma (HCC) (Ming et al, 2013), hepatic injury following hemorrhagic shock (Liu et al, 2017), schistosomiasis hepatic fibrosis (Li et al, 2017), and hepatitis c virus (HCV) infection (Reddy et al, 2018). However, whether Cori possesses the therapeutic potential for the treatment of NAFLD has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…Corilagin can protect against herpes simplex virus-1-induced encephalitis by reducing expression of TNF-α and NF-κB through inhibition of the TLR2 signaling pathway (13). Corilagin can suppress the interleukin-13/Janus kinase/signal transducer and activator of transcription-6 and microRNA-21/smad7/extracellular signal-regulated kinase signaling pathways in macrophages to reduce fibrosis severity (14). Corilagin has anti-oxidative and anti-inflammation function due to its suppression of expression of proinflammatory cytokines and mediators such as TNF-α, IL-6, inducible nitric oxide synthase, and cyclo-oxygenase-2 (15).…”
Section: Introductionmentioning
confidence: 99%